SPACE, ARCHITECTURE, AND POWER. THE TOP-DOWN AND BOTTOM-UP PLACEMAKING IN HISTORIC ARABIC-ISLAMIC CITIES - Sadek Ahmed Saad (Journal of Islamic Architecture, 2022)
Urban spaces are the end-product of various power deliberations and different urban processes, mainly the top-down and bottom-up. This study investigates the role of the two urban processes in placemaking in historic Arabic-Islamic cities. The investigation demonstrates each urban process's role in creating the major mosque's spatial context in Mecca, Medina, Cairo, Fes, Damascus, and Tripoli of Libya. Aiming to clear some preconceived ideas -strongly affected by the Renaissance’s spectacular values- about Arabic-Islamic urbanism, this article studied major Arab-Islamic cities in qualitative and quantitative approaches. The oldest available cartographic materials are investigated locally concerning political values and changes. Street patterns, space typology, and major mosque spatial context in historic Arabic-Islamic cities are studied, relating each type of urban process to placemaking's symbolic value. Before the end of the 17th century, historic Arabic-Islamic cities adopted a bottom-up process by taking advantage of the community's right to assert the order of their built environment. The top-down process was limited mainly to the architectural level of authoritarian mosques and their context. The ontological freedom and the right to control the place shifted due to exogenous political influences from the public to the authorities. By adopting the Renaissance's urban values, the top-down urban process expanded its domination on architectural and urban levels, shifting the mosque's function from socioeconomic to an artistic value. This adaptation was achieved by promoting the mosque as an artifact and creating a spectacular spatial context.